(untitled) (UNWE Yearbook, 2007)
A traditional understanding of monetary and institutional convergence related to the theory of optimum monetary zones (OMZ) is confined by several restraints. Firstly, it fails to allow for the condition of the monetary institutions, formal and informal alike. This type of the interpretation of convergence, which is more typical of the industrial stage, does not account for the changes which have taken place in the globalized information society. It regards convergence, above all, qualitatively as an aggregate and entirely mechanic phenomenon. Hence the idea of convergence is dissociated from reality, although it acquires certain possibilities to be gauged. This type of convergence fails to take into account the institutional characteristics and differences between individual eastern European countries, including Bulgaria.The sole yardstick to judge the efficiency of the monetary regime adopted is the extent it has served to meet the Maasricht criteria. The above weaknesses may be overcome in two ways: The first way involves considering the institutional aspects of the currency while looking at the entire framework of the “institutional monetary convergence”. The second approach involves adopting the model of institutional competition, or at least a partial institutional competition, between the monetary regimes of East European countries in the process of euro adoption (such as allowing the circulation of the euro alongside the national currency).